Arautos da crise: a cobertura da Operação Lava-Jato em Veja e CartaCapital - Fernandes, Pedro Veríssimo (2016)
This study analyses the media coverage of the Operation Carwash by the weekly brazilian media, aiming to understand how the magazines Veja and CartaCapital articulate their speeches and thus they get approached to the political forces which are in dispute in Brazil, here represented by the political, social and economic Brazilian dilemmas: a clash between an inclusive government and the other one that guarantees the historical inertia of the social apartheid. For this purpose, the study analyzed the articles which had the Operation Carwash on their weekly cover page, starting with the first issue on the subject, in 2014, to the last one in 2015. In total, 46 articles were analyzed, in which we divided in two interpretive packages: "the PT (Worker’s Party) is a corrupt party that has subdivided the Petrobras" and "the Operation has abuses." Based in the concept of political parallelism - the relationship kept between the media and the political parties or organizations, reflecting thereby the disputed speeches in the society - we show how each media articulates its speeches from specific nodal points, which totals and fixes, even momentarily, particular understandings of the reality, defining what is "inside" and what is "outside" of each discursive seam. In this sense, while Veja establishes itself in the field against the current federal government, the progressive movements and the inclusive public policies, culminating in the criminalization of PT as solely responsible for state corruption, excluding, for example, the "pemedebismo" (related to the PMDB party), CartaCapital articulates its discourse focusing on the corruption systemic, without being personalistic